Induced Models of Osteoarthritis in Animal Models: A Systematic Review - Umile Giuseppe Longo; Rocco Papalia; Sergio De Salvatore; Riccardo Picozzi; Antonio Sarubbi; Vincenzo Denaro (Biology, 2023)
The most common induction methods for OA are mechanical, surgical and chemical. However, there is not a gold standard in the choice of OA animal models, as different animals and induction methods are helpful in different contexts. Reporting the latest evidence and results in the literature could help researchers worldwide to define the most appropriate indication for OA animal-model development. This review aims to better define the most appropriate animal model for various OA conditions. The research was conducted on the following literature databases: Medline, Embase, Cinahl, Scopus, Web of Science and Google Scholar. Studies reporting cases of OA in animal models and their induction from January 2010 to July 2021 were included in the study and reviewed by two authors. The literature search retrieved 1621 articles, of which 36 met the selection criteria and were included in this review. The selected studies included 1472 animals. Of all the studies selected, 8 included information about the chemical induction of OA, 19 were focused on mechanical induction, and 9 on surgical induction. Nevertheless, it is noteworthy that several induction models, mechanical, surgical and chemical, have been proven suitable for the induction of OA in animals.